(untitled) (Experimental biology, 2015)
The objectives of this reearch was to study the antioxidant enzyme complexes that protect the plants at the cellular level, which can reveal adaptation mechanisms of plant stress tolerance. Studying the antioxidant enzyme complexes under stress environment is of great strategic importance for practical breeding.